Using 360-degree video for teaching emergency medicine during and beyond the COVID-19 pandemic - Alina Petrica; Diana Lungeanu; Alexandru Ciuta; Adina M. Marza; Mihai-Octavian Botea; Ovidiu A. Mederle (Annals of Medicine, 2021)
AbstractObjective During the COVID-19 pandemic, emergency medicine (EM) teachers had to employ innovative methods to ensure the continuity of the education process. The purpose of this study was to explore the adequacy of the 360-degree video (video 360) technology in EM education in the context of: (a) students' attitudes towards the video 360; (b) students' academic performance in their required examination at the end of the EM course compared to the assessment results of students from the previous academic year.Methods A mixed-method research project enrolled the fourth-year medical students who attended the required EM course during the first semester of the academic year 2020–2021 when all activities with undergraduate students went online and teaching scenarios recorded in the video 360 format were employed. Data collection was two-fold: (a) anonymous questionnaires, complemented with basic YouTube analytics; (b) multiple-choice questionnaires (MCQ) and oral examination, contrasting the results with those in 2019–2020. Data analysis used descriptive statistics and non-parametric methods.Results Seventy-nine students (53 females and 26 males) participated in the project and all completed the EM course. Students' interest in and their acceptance of the video 360 technology were high (total scoring in the upper 20% of the respective scales), with consistently good performance in two parallel, independent, interview-based oral/practical evaluations (Spearman correlation coefficient R = 0.665, p < .001). The majority scored over 90% in the summative MCQ, with higher values compared to their colleagues’ during the previous academic year (with on-site teaching): scoring percentages with mean ± standard deviation of 92.52 ± 4.57 and 76.67 ± 18.77, respectively.Conclusion Our project showed that the video 360 scenarios were effective in teaching EM. In the long term, employing this accessible and inexpensive educational approach would add value to on-site training by enriching the exposure to a specific ED environment.KEY MESSAGESMedical students valued the 360-degree video scenarios as contributing substantially to their EM knowledge and preparedness.Examination results confirmed the 360-degree video scenarios as viable in EM teaching.The 360-degree video technology would be a sustainable solution for hybrid medical teaching in the long term.